Phytochemical Analysis, Acute Toxicity, as well as Antihyperglycemic and Antidiabetic Activities of Corchorus olitorius L. Leaf Extracts - Rebecca Nakaziba; Aloysius Lubega; Jasper Ogwal-Okeng; Paul E. Alele (The Scientific World Journal)
Backgroundand Aim. Diabetes mellitus is a metabolic disorder that has no known cure with continuous endeavors to find a therapy for the condition. According to some studies, traditional leafy vegetables could prevent and manage diabetes by modifying the carbohydrate and lipid metabolism. In this study, a phytochemical analysis, acute toxicity, as well as antihyperglycemic and antidiabetic activity testing of the methanolic, diethyl ether, and aqueous leaf extracts of Corchorus olitorius L. was performed. Materials and Methods. Methanolic, diethyl ether, and aqueous leaf extracts of Corchorus olitorius L. were prepared by serial extraction. Phytochemical analysis was performed following standard methods. 52 mice were separated into 13 groups (A–M) of 4 and received extracts’ doses ranging from 1000 mg/kg to 5000 mg/kg for the acute toxicity testing. For the antihyperglycemic and antidiabetic activities testing, 48 rats were divided into 8 groups of 6 and received 500 mg/kg of each extract. 10 mg/kg of glibenclamide and distilled water were used as controls. Data were analyzed using Prism GraphPad version 8.0.2 (263). Results. Phytochemical analysis revealed the presence of alkaloids, reducing sugars, saponins, and terpenoids. There were no acute toxicity signs observed in this study. Corchorus olitorius L. extracts demonstrated moderate antihyperglycemic and antidiabetic activities. The methanolic extract exhibited the highest degree of antihyperglycemic activity. However, there was no statistically significant difference between the extracts and the negative control (p>0.05), but with glibenclamide (p<0.01). Conclusion. Corchorus olitorius L. is a safe and potential postprandial antidiabetic vegetable that could minimize the rise in blood glucose after a meal. We therefore recommend further investigations into the antidiabetic properties of the vegetable using purified extracts.